Strategic Control in Management: The Impact of Belief System and Diagnostic Control System on Managerial Performance - Keysha Amelia; Sri Maryati; Shelly Febriana Kartasari (Universitas KH. Abdul Chalim Mojokerto, 2025)
In carrying out business activities in the midst of intense competition, companies need a management control system that can not only oversee the implementation of strategies, but also provide direction to employees. Levers of Control (LOC) is one of the management controls. Belief System and Dignostic Control System are part of LOC. These two systems have a significant role to help improve management performance. However, in its application, it also needs to consider the role of Contigent Fit. This study aims to examine how the belief system and diagnostic control system affect managerial performance with contigent fit as a moderator. This research uses quantitative methods. This research data was obtained through questionnaire distribution techniques. The research sample was 33 respondents who worked at the Indonesia Stock Exchange Company. The results show that the belief system has a t count of 4.032 so that it has a significant effect on managerial performance. Diagnostic control system has a t count of 0.306 < 2.045 which has no effect on managerial performance. The first Contigent fit test has a significance value of 0.341> 0.05 and a calculated t value of 0.960 so that it cannot moderate the relationship between the belief system and managerial performance. Finally, the second Contigent fit test has a significance value of 0.218> 0.05 and a calculated t value of negative 1.261 so that Contigent fit cannot moderate the relationship between the diagnostic control system and managerial performance